The association between electronic cigarettes, sleep duration, and the adverse cardiovascular outcomes: Findings from behavioral risk factor surveillance system, 2020 - Liu, Xingyou; Yuan, Zhichao; Ji, Yuelong (Frontiers in Cardiovascular Medicine, 2022)
The joint effect of electronic cigarette smoking and insufficient sleep duration on cardiovascular disease (CVD) was unclear. This cross-sectional study aimed to evaluate the association between electronic cigarettes, sleep duration, and CVD risk among American adults. The participants who completed the survey from behavioral risk factor surveillance system in 2020 were included in this study. The status of electronic cigarettes smoking was divided into never, former, and current use. The duration of sleep was categorized into insufficient (<6 h), appropriate (6-9 h), excessive (>9 h) groups. The CVD group was defined as having any of heart attack, coronary heart disease, or stroke according to self-report. The multivariate logistic regression model was adopted to determine the association between electronic cigarettes, sleep duration, and the risk of CVD. Sensitivity analyzes were performed to assess the joint effects on the risk of CVD subtype, including heart attack, coronary heart disease, and strokes, respectively. Subgroup analyzes were performed to estimate the joint effects within the stratum of age group. There are 253,561 participants in the present study including 22,908 CVD patients. 61,293 participants had previously or currently used electronic cigarettes and 37,429 participants had inappropriate sleep duration. There were 10.8% increased odds of having CVD (OR=1.108, 95% CI: 1.001-1.227) for former electronic cigarettes users, compared to never-electronic cigarettes users. Insufficient and excessive sleep duration associated with increased risks of CVD (OR=1.592, 95% CI: 1.460-1.735; OR=1.523, 95% CI: 1.320-1.758). The participants with currently vaping status and lack of sleep had an 159.6% increased risk of CVD (OR=2.596, 95% CI: 1.810-3.723). Sensitivity analyzes found similar joint effects of current vaping and insufficient sleep on the risk of heart attack, coronary heart attack and stroke respectively. The subgroup analyzes across each age stratum found that the middle-aged group is most vulnerable to the joint effect of current vaping and insufficient sleep. This study found that both vaping and inappropriate sleep duration associated with CVD. Additionally, there was a significant joint effect of current vaping and insufficient sleep on the risk of CVD, especially for the middle-aged participants.